ENGLISH VS JAPANESE : THE PHONOLOGICAL SYSTEM ENGLISH LANGUAGE INTO ABSORPTION IN JAPANESE - Agung Olaf Ridho Rambe; Rahmadsyah Rangkuti (Hikari: Jurnal Bahasa dan Kebudayaan, 2022)
The purpose of this study is to explain phonological processes and phonological rules foreign language absorption words into Japanese through the study of generative phonology transformational. This study uses a qualitative descriptive method. Data sources obtained from written sources, namely in the form of words derived from a dictionary of absorption words Japanese language. The results of this study are that it is known that there are 7 phonological processes that occur on the process of absorption of English words into Japanese is as the following: (1) the process of adding the /u/ segment at the end of the word, (2) adding the /o/ segment in the end of the word, (3) the addition of the /u/ segment in the middle of the word, (4) the addition of the /o/ segment in the middle word, (5) substitution of phoneme /l/ into /r/, (6) substitution of phoneme /v/ into /b/, (7) addition segment /i/, (8) Substitute the phoneme /t/ into the phoneme /c/. The process of phonological change in the absorption of English into Japanese is influenced by internal factors namely the difference between the phonological systems found in English and Japanese.